Evaluation of anti-Mullerian hormone as parameter of ovarian function in patients with systemic lupus erythematosus: A systematic review and meta-analysis - Mukhammad Nooryanto; Wulandari Wulandari (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS